Heart rate variability, psychometric scales and vertical jump performance in volleyball athletes: home and away matches - Cardoso, Ananda Silveira; Berriel, Guilherme Pereira; Costa, Rochelle Rocha; Gerlach, Cleidir Luis; Kruel, Luiz Fernando Martins (Brazilian journal of physical education and sport, 2024)
The home advantage is very consolidated in the literature. The aim of this research was to evaluate the behavior of heart rate variability (HRV), perceived recovery status (PRS) and rating of perceived exertion (RPE) and vertical jumps performance in professional volleyball athletes in home and away matches. Nine male professional volleyball athletes (25,66 ± 5,7 anos, 97,81 ± 8,65 Kg and 200,94 ± 5,19 cm), with experience in national and international competitions participated in the study. HRV and PRS were evaluated in the morning of the matches. RPE was collected immediately after the matches. Jump performance was monitored during the matches. The data was grouped by home matches and away matches and the t test or Wilcoxon test was performed for comparison. Significance level adopted was α ≤ 0.05. Effect size was analyzed by Cohen’s d coefficient. O nível de significância adotado foi α ≤ 0,05. There were no significant difference in HRV, PRS, RPE, jumps height and number of jumps evaluated in home matches and away matches. We conclude that despite the home advantage consolidated in the literature and possible adverse effects of travel on away matches, the VFC, PRS, RPE and jump performance were similar in the two situations evaluated.